ANALISIS PENGARUH FAKTOR NILAI, CITRA, KEPUASAN YANG DIRASAKAN, LAYANAN KONSUMEN, JAMINAN TERHADAP LOYALITAS KONSUMEN KECAP ABC DI KOTA PALEMBANG - zakaria Wahab; Pri Harum Belawati (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2009)
This research aimed to 1) reveal how much the effect of value, image, satisfaction, customer services, and warranty on customer loyalty of ABC soya in Palembang, and 2) know dominant variables affecting the customer loyalty of ABC soya in Palembang. The method used in this study was causal method. The number of the samples are 120 respondents. The data collection techniques used are quesionaires, and interviews. And then, analyzed using multiple linier regression with statistical product for special solution (SPSS) for windows version 13,0.This research results indicated that factor of value, image, satisfaction, customer services, and warranty has positive effect on customer loyalty of ABC soya in Palembang that is 34.3%, the rest are caused by the others factor , and partially the factor of satisfaction had a dominant effects on costumer loyalty of ABC soya in Palembang.Key words: customer loyalty, value, image, satisfaction, customer services, warranty